Applicability of garnet-cordierite (Gt-Crd) geothermometer - Thomas, Harel Thomas; Rana, Haritabh; Mishra, Anju (Journal of Nepal Geological Society, 2020)
The garnet-cordierite pairs are commonly found in the assemblages of granulites and hence are suitable for estimating equilibrium temperature of these metamorphic rocks. At present, there are many calibrations of garnet - cordierite (Gt-Crd) thermometer that may confuse geologists in choosing a reliable thermometer. To test the accuracy of the garnet - cordierite thermometers, we have applied eleven models formulated by a number of researchers since (1976) till date. We have collected 70 samples from the literature all over the world, which has been processed through “Gt-Crd.EXE” software. Based on the present study, we have identified a set of the best among all the eleven models which were considered under this comparative study. We have concluded that the five garnet-cordierite thermometers are the most valid and reliable of this kind of thermometer (Holdaway and Lee, 1977; Perchuk et al. 1985; Thompson, 1976; Wells,1979 and Aranovich and Podlesskii ,1989).